Quantum Boltzmann equation for strongly correlated systems : comparison to dynamical mean field theory - Wais, M. (2018)
We investigate the potential of a quantum Boltzmann equation without momentum conservation for description of strongly correlated electron systems out of equilibrium. In a spirit similar to dynamical mean field theory (DMFT), the momentum conservation of the electron-electron scattering is neglected, which yields a time-dependent occupation function for the equilibrium spectral function, even in cases where well-defined quasiparticles do not exist. The main assumption of this method is that the spectral function remains sufficiently rigid under the nonequilibrium evolution. We compare the result of the quantum Boltzmann equation to nonequilibrium DMFT simulations for the case of photocarrier relaxation in Mott insulators, where processes on very different timescales emerge, i.e., impact ionization, intra-Hubbard-band thermalization, and full thermalization. Since quantum Boltzmann simulations without momentum conservation are computationally cheaper than nonequilibrium DMFT, this method allows the simulation of more complicated systems or devices, and to access much longer times.